PENERAPAN MEDIA POP UP BOOK BERBANTUAN LKS CROSSWORD PUZZLE UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X DI SMA NEGERI 1 PANDAWAI - Dembi Tamar, Debora; Makaborang, Yohana; Rambu Hada Enda, Riwa (Jurnal Biogenerasi, 2025)
The purpose of this study was to improve student learning outcomes through the application of pop-up book media assisted by LKS Crossword Puzzle. This classroom action research (CAR) used a descriptive quantitative approach. In the pre-cycle, cycle I and cycle II. 36 students were involved in the study. Multiple choice questions (posttest), observation, and documentation were the data collection methods used. The cognitive learning outcomes of students in the pre-cycle showed an average value of 60.69, with the percentage of students achieving KKM of 36%, while 64% of students did not achieve KKM. The affective learning outcomes of students showed an average value of 56.56, with the percentage of students who successfully achieved completion reaching 28%, while the percentage of students who had not completed was 72%, which was categorized as low. In cycle I, the students' learning outcomes obtained an average cognitive value of 81.19; students who completed KKM were 81%, while 19% did not complete, and the affective learning outcomes of students obtained an average value of 76.86 with 67%, and students who did not complete were 33%. However, the increase in educational outcomes of students in cycle I. In cycle II, the average cognitive value achieved by students was 95.22, with the proportion of students who achieved KKM reaching 94%, while the number of students who did not meet KKM was 6%, The affective learning outcomes of students also increased significantly, with an average value of 92.3 and students who achieved 94% of students who did not 6%.